EXPLORING THE IMPACT OF OCCUPATIONAL DRAWING THERAPY ON REDUCING AUDITORY HALLUCINATIONS AT RS. JIWA DAERAH SURAKARTA - Angelia, Lavinna Agatha; Yunitasari, Pritta (Jurnal Keperawatan PPNI Jawa Barat, 2024)
Background : Hallucinations are the client's wrong perception of the real environment and the loss of human ability to be able to distinguish internal (thought) and external (external) stimuli. Non-pharmacological treatment that can be done to reduce changes in auditory hallucinations is by applying occupational drawing therapy. Method : The data collection method used in this scientific paper uses descriptive method. Result : The application of occupational drawing therapy in the Abimanyu Ward was carried out for four days. The results of the study on Mr. S has signs and symptoms of auditory hallucinations. Before the nursing action on the application of occupational drawing therapy was carried out there were ten signs and symptoms of hallucinations, after the implementation of the application of occupational drawing therapy there were five signs and symptoms on the fourth day. Conclusion: The author has real experience in providing occupational drawing therapy to patients with auditory hallucinations.